Estimativas de expectativa de vida em diferentes contextos de saúde: aplicação do método de Sullivan para idosos de pequenos municípios - Bortoluzzi, Emanuelly Casal (2017)
The world population’s life expectation is increasing; however the quality of life of the current years is an aspect to be observed. By this point, the functional capacity and the presence of chronic diseases are important health’s conditions to be considered, in view of negative repercussions to the person, to the family and to the health system. Therefore, among the estimate methods of general life expectation and with determined health conditions, the Sullivan’s method shows up as a simple and easy possibility to be applied. Nevertheless, these estimates were not founded in resident elderly from small cities, places where life conditions and routine of elderly may be different from the ones who live in big cities. Objective: Estimating general life’s expectation, free or not from functional incapacity, chronic diseases and multimorbity in resident elderly of small cities. Method: It’s about an estimate study of life’s expectation by the Sullivan’s method. Information was used from two cross-sectioned studies, by population base, information related to the number of the city’s habitants in a determined period of information and death collection in a period of five years, aiming at the decrease of possible seasonal effects. Results: The founded estimate for women about 60 years was 28,7 years, 20,4 with multimorbity of these, 14,8 years with three or more chronic disease, 13,5 years with incapacity for instrumental activities and 5,1 with incapacity for life’s routine basic activities. With men, the research shows that the ones with 60 years can live for 24,7 years, of which 2,8 years with incapacity for basic activities, 7,9 years with incapacity for instrumental activities, 14,9 with multimorbity and 8,9 years with three or more chronic disease. About the differences between both sexes, women show a number statistically higher for years to be lived with incapacity to instrumental activities of daily life and multimorbity. Conclusion: Women possess a higher estimative of life’s expectation than men; however, men will possess a higher proportion of years to be lived without functional incapacity to basic and instrumental activities in daily life and greater number of chronic disease.